Functional MRI study of the cognitive generation of affect. - Teasdale, John D.; Howard, Robert J.; Cox, Sally G. (American Journal of Psychiatry, 1999)
|WbObjective:[|WB] The authors investigated, by whole brain functional magnetic resonance imaging (MRI), the neural substrate underlying processing of emotion-related meanings. |WbMethod:[|WB] Six healthy subjects underwent functional MRI while viewing 1) alternating blocks of pairs of pictures and captions evoking negative feelings and the same materials irrelevantly paired to produce less emotion (reference pairs); 2) alternating blocks of picture-caption pairs evoking positive feelings and the same materials irrelevantly paired to produce less emotion; and 3) alternating blocks of picture-caption pairs evoking positive feelings and picture-caption pairs evoking negative feelings. |WbResults:[|WB] Compared with the reference picture-caption pairs, negative pairs activated the right medial and middle frontal gyri, right anterior cingulate gyrus, and right thalamus. Compared with the reference picture-caption pairs, positive pairs activated the right and left insula, right inferior frontal gyrus, left splenium, and left precuneus. Compared with the negative picture-caption pairs, positive pairs activated the right and left medial frontal gyri, right anterior cingulate gyrus, right precentral gyrus, and left caudate. |WbConclusions:[|WB] Contrasts of both 1) negative and reference picture-caption pairs and 2) positive and negative picture-caption pairs activated networks involving similar areas in the medial frontal gyrus (Brodmann's area 9) and right anterior cingulate gyrus (areas 24 and 32). The area 9 sites activated are strikingly similar to sites activated in related positron emission tomography experiments. Activation of these same sites by a range of evoked affects, elicited by different methods, is consistent with areas within the medial prefrontal cortex mediating the processing of affect-related meanings, a process common to many forms of emotion production. Reprinted by permission of the publisher.